Mir-629 Repressed LATS2 Expression and Promoted the Proliferation of Prostate Cancer Cells - Li, Yuqiao; Zeng, Sha; Cao, Longbin (Hormone and Metabolic Research, 2023)
MicroRNAs (miRNAs) have been discovered to play critical role in regulating prostate cancer (PC) progression. The function role of miR-629 in tumor progression of PC has not been studied. Here, we found that miR-629 was markedly upregulated in PC as determined using the cancer genome atlas (TCGA) dataset, clinical tissues, and cell lines. Functional analysis (MTT assays, colony formation assays, soft agar growth assay and BrdU incorporation assay) indicated that overexpression of miR-629 was drastically promoted, while miR-629-in significantly suppressed cell proliferation. LATS2 was predicted as a direct target of miR-629 and was confirmed by western blot and dual luciferase assay. Through downregulation of large tumor suppressor 2 (LATS2) by overexpression of miR-629, the p21 mRNA and protein were decreased while the Cyclin D3 mRNA and protein were enhanced, suggesting promoting of cell proliferation process. Additionally, knockdown of LATS2 reversed the inhibitory effect by miR-629-in in PC. Our study indicated that miR-629 might serve as a new promising target for PC treatment.
Keywords: miR-629; prostate cancer; cell proliferation; LATS2